AB0063 Gammadelta t cells and their intracellular cytokine profile in peripheral blood of patients with systemic lupus erythematosus. (23rd January 2014) - Lu, Z.; Li, X.; Sun, L.
Abstract : Background: Gammadelta T cells represent a minor population of human peripheral blood T lymphocytes. As very rapid cytokine-producing cells, gammadelta T cells can regulate other lymphocytes activation and assist their local inflammatory function, thus are involved in some autoimmune diseases. Systemic lupus erythematosus (SLE) is a multi-organ damage autoimmune disease characterized by lymphocytes dysfunction and aberrant cytokines production. Objectives: The aim of this study was to detect gammadelta T cells numbers in the peripheral blood mononuclear cells (PBMCs) and analyze their intracellular cytokines profile (IFN-γ, IL-4, IL-10, IL-17, TGF-β). Methods: Gammadelta T cells were detected in peripheral blood from 42 SLE patients and 20 normal controls by flow cytometry (FACS). Lupus disease activity was evaluated with a SLEDAI (Systemic Lupus Erythematosus Disease Activity Index) score. Active SLE was defined as SLEDAI≥8. Anniex-V/PI double-staining FACS analysis was employed to observe the proportion of the apoptotic gammadelta T cellsin 6 active SLE patients and 6 normal controls, respectively. The percentages of cytoplasmic cytokines including IFN-γ, IL-4, IL-10, IL-17 and TGF-β were examined in20 SLE patients and 10 normal controls by using FACS anlysis. Results: The percentages of gammadelta T cells were remarkably down-regulated in active SLE patients (2.96±1.84%, n=30) compared with that of inactive (5.31±3.05%, n=12) and normal controls (6.83±2.85%, n=20, both p<0.01). The absolute number of gammadelta T cells decreased significantly in active SLE patients (1.72±1.58×10 7 /L, n=30) than that in inactive SLE (5.27±3.60×10 7 /L, n=12, p<0.01), both lower than in normal controls (10.07±4.99 ×10 7 /L, n=20, both p<0.01). There was increased gammadelta T cells apoptosis (17.03±8.71%, n=6) in SLE patients than in normal controls (6.67±1.18%, n=6, p<0.05). The positive rate of gammadelta T intracellular IFN-γ, IL-4, IL-10 and TGF-β production in 20 SLE patients were 33.19±20.20%, 1.04±0.93%, 1.91±0.98% and 2.20±1.97%, significantly higher than that of 10 normal controls (IFN-γ: 5.87±4.63%, IL-4:0.30±0.34%, IL-10:0.18±0.31%, TGF-β: 0.21±0.22%, all p<0.01). While there were no differences in the percentages of IL-17-positive gammadelta T cells between SLE patients (0.14±0.24%, n=20) and normal controls (0.18±0.31%, n=10). Conclusions: Gammadelta T cells are down-regulated in SLE partly due to excessive apoptosis. GammadeltaT cells secret both pro- and anti-inflammatory cytokinesin SLE microenvironment, suggesting these cells participate in both the regulation and the propagation of lupus. Disclosure of Interest: None Declared